Economic and managerial transformation of the developer's business portfolio in the context of innovative development and operational multistructurality - Kryshtal , H.; Rachkivska , K.; Yakymchuk , I.; Maximyuk , J; Mokrotskyi , O.; Lutsenko , B. (Ways to Improve Construction Efficiency, 2024)
The article explores the conceptual and applied foundations of the economic and managerial transformation of the business portfolio of developer enterprises in the context of increasing complexity, multiproject orientation, and digital adaptation of the modern construction environment. The authors emphasize the multiproject nature of construction development as a prerequisite for shaping new management strategies based on analytical support, indicative control, and flexible digital monitoring. The study highlights the role of project attribution in building an effective enterprise portfolio, taking into account such parameters as project type, life cycle stage, institutional conditions, innovation orientation, sources of financing, and the degree of digitalization. The research conceptualizes analytical support for the multiproject environment as an element of managerial maturity, ensuring adaptability and strategic resilience for the developer. The evolution of analytical approaches is revealed — from financial-budgetary models to platform-based knowledge management systems built on real-time data, BIM modeling, digital twins, and multidimensional visualization. Three directions for the development of the digital diagnostics system are identified: digital-platform-based, institutional-systemic, and methodological. The components of the integrated analytical system are described, including data hubs, indicative modules, multilevel risk analysis, digital dashboards, scenario planning tools, and stakeholder interaction mechanisms. It is concluded that analytical and digital transformation of the developer's business portfolio serves as a key tool for gaining competitive advantages in the turbulent and digitalized landscape of the modern market.